2017
DOI: 10.3390/rs9050507
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Seasonal Glacier-Wide Surface Mass Balance Quantified from Changes in Glacier Surface State: A Review on Existing Methods Using Optical Satellite Imagery

Abstract: Glaciers are one of the terrestrial essential climate variables (ECVs) as they respond very sensitively to climate change. A key driver of their response is the glacier surface mass balance that is typically derived from field measurements. It deserves to be quantified over long time scales to better understand the accumulation and ablation processes at the glacier surface and their relationships with inter-annual changes in meteorological conditions and long-term climate changes. Glaciers with in situ monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 58 publications
(101 reference statements)
6
51
0
3
Order By: Relevance
“…Larger-scale studies and multi-variable correlations in between morpho-topographic features could be for instance envisaged. Rabatel et al (2017) recently proposed an alternative approach to reconstruct the annual mass balance of unmonitored glacier on the basis of the albedo method. This approach relies on the ELA method (Rabatel et al, 2005), but using the remotely sensed monitored α min a together with the AAR, the glacier hypsometry, and the regional SMB elevation gradient (which is the annual SMB gradient in the vicinity of the glacier ELA).…”
Section: Limits Of the Albedo Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger-scale studies and multi-variable correlations in between morpho-topographic features could be for instance envisaged. Rabatel et al (2017) recently proposed an alternative approach to reconstruct the annual mass balance of unmonitored glacier on the basis of the albedo method. This approach relies on the ELA method (Rabatel et al, 2005), but using the remotely sensed monitored α min a together with the AAR, the glacier hypsometry, and the regional SMB elevation gradient (which is the annual SMB gradient in the vicinity of the glacier ELA).…”
Section: Limits Of the Albedo Methodsmentioning
confidence: 99%
“…This approach relies on the ELA method (Rabatel et al, 2005), but using the remotely sensed monitored α min a together with the AAR, the glacier hypsometry, and the regional SMB elevation gradient (which is the annual SMB gradient in the vicinity of the glacier ELA). For an exhaustive description of this approach, see Rabatel et al (2017).…”
Section: Limits Of the Albedo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The snow line is recognized as a valuable proxy for glacier mass balance (LaChapelle, 1962;Lliboutry, 1965;Braithwaite, 1984;Kulkarni, 2012;Rabatel et al, 2017). Different methods have been developed to use the end-of-summer snow line observed on air-and space-borne data, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, remote sensing techniques have proven to be useful for glacier monitoring, since the available satellite sensors are increasing and their spatial, radiometric and temporal resolutions are improved [11,12].Glacier mass fluctuations can be calculated by using several parameters derived from remote sensing images, e.g., the difference between two digital elevation models (DEMs) at different times [13][14][15][16], the equilibrium-line altitude (ELA) at the end of the hydrological year [12,17,18], the accumulation-area ratio (AAR) [19,20] over a glacier, and the average glacier surface albedo [21][22][23][24]. Among these glacier properties, recent studies have revealed that the variation of glacier-wide surface albedo has shown outstanding potentials in obtaining annual or seasonal mass balance, because minimum surface albedo was directly related to AAR and ELA.…”
Section: Introductionmentioning
confidence: 99%